Characterization of Spleen Transcriptome and Immunity Against Avian Colibacillosis After Immunization With Recombinant Attenuated Salmonella Vaccine Strains - Stromberg, Zachary R.; Van Goor, Angelica; Redweik, Graham A. J.; Mellata, Melha (Frontiers in Veterinary Science, 2018)
Avian pathogenic Escherichia coli (APEC) causes extraintestinal infections in poultry. Vaccines targeting APEC in chickens have been partially successful, but many lack heterologous protection. Recombinant attenuated Salmonella vaccine (RASV) strains can induce broad immunity against Salmonella and be modified to deliver E. coli antigens. Along with vaccine characteristics, understanding the host response is crucial for developing improved vaccines. The objectives of this study were to evaluate host responses to vaccination with an RASV producing E. coli common pilus (ECP) and assess protection against APEC infection in chickens. Four-day-old White Leghorn chickens were unvaccinated or orally vaccinated and boosted two weeks later with RASV 8025(pYA3337), RASV 8025(pYA4428) carrying ecp operon genes, or a combination of 8025(pYA3337) and 8025(pYA4428) (Combo). To assess host responses, serum IgY and intestinal IgA antibody titers were measured, and spleen samples (n=4/group) were collected from unvaccinated and Combo vaccinated four-week-old chickens for RNA-seq. Vaccine protection potential against Salmonella and APEC was evaluated in vitro using bacterial inhibition assays. Five-week-old chickens were challenged via air sac with either an APEC O2 or O78 strain. E. coli was enumerated from internal organs, and gross colibacillosis lesions were scored at necropsy. RASV immunized chickens elicited anti-E. coli antibodies. The spleen transcriptome revealed that 93% (89/96) of differentially expressed genes (DEG) were more highly expressed in Combo vaccinated compared to unvaccinated chickens, with signal as the most significantly impacted category. RNA-seq analysis also revealed altered cellular and metabolic processes, response to stimulus after vaccination, and immune system processes. Six DEG including genes linked to transcription regulation, actin cytoskeleton, and signaling were highly positively correlated with antibody levels. Samples from RASV immunized chickens showed protection potential against Salmonella strains using in vitro assays, but a variable response was found for APEC strains. After APEC challenges, significant differences were not detected for bacterial loads or gross lesions scores, but 8025(pYA3337) immunized and 8025(pYA4428) immunized chickens had significantly fewer number of APEC-O2-positive samples than unvaccinated chickens. This study shows that RASVs can prime the immune system for APEC infection, and is a first step toward developing improved therapeutics for APEC infections in chickens.